Incomplete penetrance for isolated congenital asplenia in humans with mutations in translated and untranslated RPSA exons - Bolze, A; Boisson, B; Bosch, B; Antipenko, A; Bouaziz, M; Sackstein, P; Chaker-Margot, M; Barlogis, V; Briggs, T; Colino, E; Elmore, A; Fischer, A; et al. (National Academy of Sciences, 2018)
Isolated congenital asplenia (ICA) is the only known human developmental defect exclusively affecting a lymphoid organ. In 2013, we showed that private deleterious mutations in the protein-coding region of RPSA, encoding ribosomal protein SA, caused ICA by haploinsufficiency with complete penetrance. We reported seven heterozygous protein-coding mutations in 8 of the 23 kindreds studied, including 6 of the 8 multiplex kindreds. We have since enrolled 33 new kindreds, 5 of which are multiplex. We describe here 11 new heterozygous ICA-causing RPSA protein-coding mutations, and the first two mutations in the 5′-UTR of this gene, which disrupt mRNA splicing. Overall, 40 of the 73 ICA patients (55%) and 23 of the 56 kindreds (41%) carry mutations located in translated or untranslated exons of RPSA. Eleven of the 43 kindreds affected by sporadic disease (26%) carry RPSA mutations, whereas 12 of the 13 multiplex kindreds (92%) carry RPSA mutations. We also report that 6 of 18 (33%) protein-coding mutations and the two (100%) 5′-UTR mutations display incomplete penetrance. Three mutations were identified in two independent kindreds, due to a hotspot or a founder effect. Finally, RPSA ICA-causing mutations were demonstrated to be de novo in 7 of the 23 probands. Mutations in RPSA exons can affect the translated or untranslated regions and can underlie ICA with complete or incomplete penetrance.